The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.5937/tmg1601020k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of obesity on serum uric acid level in postmenopausal women

Abstract: (1) DOM ZDRAVLJA, PODGORICA, CRNA GORA, (2) FARMACEUTSKI FAKULTET, UNIVERZITET U BEOGRADU, SRBIJA Sažetak :Cilj: U fiziološkim koncentracijama mokraćna kiselina (MK) je moćan neenzimski antioksidans. Ipak, u povišenoj koncentraciji, MK ispoljava oksidativno dejstvo, dovodeći do oštećenja ćelije sa posledičnim rizikom za nastanak brojnih oboljenja. Mehanizam putem kojeg povećana koncentracija MK dovodi do oboljenja uzrokovanih gojaznošću nije u potpunosti razjašnjen. Zato je cilj naše studije da se ispita utica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…In addition to this, we previously reported a significant relationship between serum uric acid level and anthropometric parameters, stronger with WC than with BMI, implicating that visceral adipose tissue is the main determinant of serum uric acid level [26]. Furthermore, in our previous study we showed that uric acid correlated with the majority of components of MetS, including insulin resistance.…”
Section: Discussionsupporting
confidence: 68%
“…In addition to this, we previously reported a significant relationship between serum uric acid level and anthropometric parameters, stronger with WC than with BMI, implicating that visceral adipose tissue is the main determinant of serum uric acid level [26]. Furthermore, in our previous study we showed that uric acid correlated with the majority of components of MetS, including insulin resistance.…”
Section: Discussionsupporting
confidence: 68%
“…(19) pokazala da i predgojazna/gojazna deca uzrasta 6-24 meseca imaju više vrednosti leptina i kortizola, a niže aktivnosti CAT i SOD u poređenju sa kontrolnom grupom. Mnoge studije opisuju izmenjenu antioksidativnu zaštitu kod gojaznih osoba (20,21,22,23). Niža koncentracija bilirubina, koji ispoljava antioksidativno i antiinflamatorno dejstvo, je zabeležena kod gojaznih adolescentkinja.…”
Section: Masno Tkivo Kao Značajan Izvor Slobodnih Radikalaunclassified
“…The current cross-sectional study derived from our previous works investigating the utility of examining cardiometabolic markers in postmenopausal women [1][2][3][4][5][6][7]. A total of 150 postmenopausal women nontreated with medications (among them 44.7% hypertensive) were included in cross-sectional study.…”
Section: Study Populationmentioning
confidence: 99%
“…It is speculated that redistribution of adipose tissue towards visceral region, due to hormonal changes may be the main pathogenic entity, consequently leading to increased cardiometabolic risk [4] in postmenopause. Increased visceral fat mass is a source of proinflammatory adipocytokines [5][6][7][8], exerting a low-grade inflammation environment which could predispose to the future hypertension occurrence [9]. In addition, increased abdominal fat mass is accompanied with increased insulin resistance [4,8].…”
Section: Introductionmentioning
confidence: 99%